2010
DOI: 10.1126/science.1183424
|View full text |Cite|
|
Sign up to set email alerts
|

Arsenic Trioxide Controls the Fate of the PML-RARα Oncoprotein by Directly Binding PML

Abstract: Arsenic, an ancient drug used in traditional Chinese medicine, has attracted worldwide interest because it shows substantial anticancer activity in patients with acute promyelocytic leukemia (APL). Arsenic trioxide (As2O3) exerts its therapeutic effect by promoting degradation of an oncogenic protein that drives the growth of APL cells, PML-RARalpha (a fusion protein containing sequences from the PML zinc finger protein and retinoic acid receptor alpha). PML and PML-RARalpha degradation is triggered by their S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
554
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 716 publications
(577 citation statements)
references
References 28 publications
17
554
2
4
Order By: Relevance
“…As 2 O 3 exerts its powerful therapeutic effect in APL by promoting the degradation of a specific oncogenic protein, the so‐called PML‐RAR α fusion protein (Emadi and Gore 2010; Zhang et al. 2010). In contrast, regarding the other hematologic malignancies, this drug could be effective by activating several pathways leading to cancer cell apoptosis including mitochondrial dysfunction, oxidative stress, and DNA damage (Pelicano et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As 2 O 3 exerts its powerful therapeutic effect in APL by promoting the degradation of a specific oncogenic protein, the so‐called PML‐RAR α fusion protein (Emadi and Gore 2010; Zhang et al. 2010). In contrast, regarding the other hematologic malignancies, this drug could be effective by activating several pathways leading to cancer cell apoptosis including mitochondrial dysfunction, oxidative stress, and DNA damage (Pelicano et al.…”
Section: Introductionmentioning
confidence: 99%
“…2007; Zhang et al. 2010). Some studies also suggested that ER stress could be involved in the anticancer action of arsenic trioxide (Du et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, arsenic is also a novel promising anticancer agent for treating acute promyelocytic leukemia (APL) 3 and other tumors with mild adverse effects (27)(28)(29)(30). Studies showed that arsenic trioxide produces remissions in patients with APL at least in part through degradation of the aberrant PML-retinoic acid receptor ␣ (PML-RAR␣) fusion protein (32,33). Upon arsenic trioxide exposure, PML undergoes intermolecular disulfide formation and directly binds to arsenic via cysteine residues in zinc fingers located within the RBCC domain of PML and PML-RAR␣.…”
mentioning
confidence: 99%
“…Upon arsenic trioxide exposure, PML undergoes intermolecular disulfide formation and directly binds to arsenic via cysteine residues in zinc fingers located within the RBCC domain of PML and PML-RAR␣. Disulfide-linked PML or PML-RAR␣ multimers form nuclear matrix-associated nuclear bodies and become sumoylated and then degraded (32,33). In addition to PML-RAR␣, several other proteins with a high content of cysteine residues and vicinal thiol groups are also targets of arsenic, such as AML1/MDS1/EVI1 protein produced from a fusion gene generated by a t(3;21)(q26;q22) translocation in chronic myelogenous leukemia (34), Gli2 transcriptional effector in the Hedgehog pathway (35), AKT protein (36), BCR/ABL protein produced from a fusion gene generated by a t(9;22) chromosomal translocation in chronic myelogenous leukemia (37), and survivin (38).…”
mentioning
confidence: 99%
“…In the April 9 th issue of the journal, Science , Zhang et al . provided new and convincing evidence on how AT, an ancient poisonous medicine, plays the tricks on the oncoprotein, PML-RARα, and sheds lights on how a poisonous kiss leads to the sweet fruit [1]. …”
Section: Editorialmentioning
confidence: 99%